Different catalytic behavior of Pd/Palygorskite catalysts for semi-hydrogenation of acetylene - Dai, Hui; Xiao, Xin; Huang, Lihong; Zhou, Changjian; Deng, Jie (Applied clay science, 2021)
The development of an efficient and cost-effective catalyst for selective hydrogenation of acetylene is an important subject in the polyethylene industry. The activity of the Pd-based catalyst is affected by the support. In this paper, palygorskite (Pal) was modified by the different roasting atmosphere (NH3 or air), and the catalytic performance of supported ultralow-low content Pd-based catalyst for the semi-hydrogenation of acetylene was studied. Among them, the acetylene activation energy of air-treated Pd catalyst is higher than that of NH3 catalyst. The carrier was further studied by N2 adsorption/desorption, X-ray diffraction (XRD), CO chemisorption, high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM), temperature-programmed chemisorption, X-ray photoelectron spectroscopy (XPS) and thermogravimetric analysis (TGA). The results show that Pal calcined with NH3 is beneficial to the dispersion of Pd nanoparticles on the carrier and inhibits the formation of β-PdHX, leading to higher ethylene selectivity. Due to the stable selectivity of ultra-low load Pd/N-Pal catalyst, it is probably a green, effective, cost-effective, and readily available catalyst with promising prospects in the hydrogenation industry. [Display omitted] •The Pd based catalyst was obtained by using palygorskite (Pal) as carrier.•Pd content of catalyst was ultra-low for selective hydrogenation reaction.•The pyridinic-N and pyrrolic-N were the anchoring sites for Pd nanoparticles.•Pd/N-Pal exhibits excellent activity for semi-hydrogenation of acetylene.